2013
DOI: 10.1002/esp.3491
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of pulsed versus chronic sand inputs on salmonid spawning habitat in a low‐gradient gravel‐bed river

Abstract: It is widely recognized that high supplies of fine sediment, largely sand, can negatively impact the aquatic habitat quality of gravel-bed rivers, but effects of the style of input (chronic vs. pulsed) have not been examined quantitatively. We hypothesize that a continuous (i.e. chronic) supply of sand will be more detrimental to the quality of aquatic habitat than an instantaneous sand pulse equal to the integrated volume of the chronic supply. We investigate this issue by applying a two-dimensional numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 60 publications
5
42
0
1
Order By: Relevance
“…This association is shown more clearly in Figure , where infiltration rate is plotted against discharge. When the mean data is considered, a strong dependence between total deposition and discharge was shown (r 2 = 0.7, p < .01), a finding also noted by Maturana et al (). Extrapolation of the regression equation suggested that fine bedload movement was initiated at discharges in excess of 0.7 m 3 s −1 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This association is shown more clearly in Figure , where infiltration rate is plotted against discharge. When the mean data is considered, a strong dependence between total deposition and discharge was shown (r 2 = 0.7, p < .01), a finding also noted by Maturana et al (). Extrapolation of the regression equation suggested that fine bedload movement was initiated at discharges in excess of 0.7 m 3 s −1 .…”
Section: Resultssupporting
confidence: 77%
“…The clear association between infiltration rates and discharge, with greatest rates of infiltration being associated with high winter flows is a feature supported by other investigations (Maturana et al, ). Higher winter discharges have the competence to transport greater quantities of bedload; however, the supply of sand is also a key factor.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This may involve mimicking the underlying process through novel disturbances (e.g., cutting trees to simulate wildfire loss that initiates stand dynamics but also leaving the forest to recover) or restoring natural disturbance regimes. Human actions interrupt migratory life histories of aquatic organisms through road crossings and other barriers (Dunham et al 2003;Rieman et al 2003); alter sediment production and transport regimes (Istanbulluoglu et al 2004;Goode et al 2012;Maturana et al 2014); change flow, bed scour, and temperature regimes (Marks et al 1998;Lessard and Hayes 2003;Tonina et al 2008); and alter wood loading and channel morphology (Montgomery et al 1995;Wood-Smith and Buffington 1996;Benda et al 2003;May and Gresswell 2003). For example, fire-related management activities may disrupt watershed processes and degrade habitat for sensitive fishes (Rieman et al 2010).…”
Section: Box 1 the Role Of Natural Disturbance And Renewal In Aquaticmentioning
confidence: 99%
“…Allowing natural disturbance processes to play out, however, may sometimes be unfeasible because of other societal demands on forests and water. For example, chronic supplies of fine sediment from forest roads can have a greater and longer-lasting impact on salmonid spawning habitats than an equal volume of material introduced as a sediment pulse by a naturally occurring debris flow or landslide (Maturana et al 2014). Human influences offer a means of promoting disturbance and biological response but frequently differ from natural disturbances in the timing, magnitude, spatial extent, and nature of the disturbance (Lindenmayer and Franklin 2002;Hessburg et al 2005), and may result in ecosystem structure and connectivity that differ from natural conditions (Stanford and Ward 1992).…”
Section: Box 1 the Role Of Natural Disturbance And Renewal In Aquaticmentioning
confidence: 99%